SCREENING KESEHATAN BAGI SANTRI DAN GURU PENDIDIK DI PONDOK PESANTREN - Syakura , Abdan; Noviandry, R , Hilmah; Fauziyah, Endang; Rahman, Taufiqur; Nindawi, Nindawi; Pramesthi V.P, Nindi; Oktavisa Denta, Anggeria; Christiana, Elisa; Suraying, Suraying; Renidya, A, Renidya, A; Khalilah, Nur; Andayani, Qurnia; Ferdina, Cucun Setya; Novitasari, Isnaini; Jufriyanto, M.; DJMN, Meithun (LPPM Universitas Bina Bangsa, 2024)
Islamic boarding schools in East Java are generally crowded, with students living in one dormitory with limited facilities. Growth and development health issues in pesantren students are also an important concern, given the living conditions in pesantren that can affect the physical and mental development of santri. One problem that often occurs is stunting or stunted growth due to lack of adequate nutritional intake during childhood and adolescence. The methods used in this community service activity are lectures and physical examinations. The measuring instrument used is a multiplechoice type closedended questionnaire. Respondents were asked to fill out a questionnaire before counseling (pre-test) and after counseling (post-test). Then the data was analyzed using the average and delta calculation method with the results of the pretest average of 72.60 and postest of 87.23. In addition, the results of the health examination consisted of visus examination, height, weight, and other health examinations. In general, the results of the examination of participants showed that a small proportion experienced health problems, so it is hoped that the pesantren will further improve health services and facilities in the pesantren environment